2020
DOI: 10.3390/molecules25235754
|View full text |Cite
|
Sign up to set email alerts
|

Co-Digestion of Grape Marc and Cheese Whey at High Total Solids Holds Potential for Sustained Bioenergy Generation

Abstract: At the end of fermentation, wine contains approximately 20% (w/v) of solid material, known as grape marc (GM), produced at a yield of 2 t/ha. Cheese manufacture produces cheese whey (CW), which is over 80% of the processed milk, per unit volume. Both waste types represent an important fraction of the organic waste being disposed of by the wine and dairy industries. The objective of this study was to investigate the bioenergy potential through anaerobic codigestion of these waste streams. The best bioenergy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Regarding research that has been developed about the use of CW and its connections to the principles of the CE, it was found that only eight articles have been published during the period under consideration [9,16,[41][42][43]. Of these publications, seven are from Europe (Spain, Greece, Ireland, Italy, Portugal, the United Kingdom, and the Czech Republic) and one from Oceania (Australia).…”
Section: Geographical Location Of the Studies And Its Evolution Over ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding research that has been developed about the use of CW and its connections to the principles of the CE, it was found that only eight articles have been published during the period under consideration [9,16,[41][42][43]. Of these publications, seven are from Europe (Spain, Greece, Ireland, Italy, Portugal, the United Kingdom, and the Czech Republic) and one from Oceania (Australia).…”
Section: Geographical Location Of the Studies And Its Evolution Over ...mentioning
confidence: 99%
“…It is observed that the author Rodrigues J.A.D., Ratusznei, S.M., Lovato, G., and Albanez, R. are the ones who hav Studies related to CW anaerobic degradation, from the perspective of the CE, appeared for the first time in 2017 [41]. However, it was only in 2020 when the largest number of publications appeared [9,16,42,43,48]. This finding allows the inference that the subject has not been extensively studied, which represents an opportunity for research in the context of Latin America and especially in countries such as Colombia, with a long tradition of dairy industries.…”
Section: Author and Word Co-occurrence Top Journals Main Articles And...mentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement in reactor capacity allows the treatment of co-substrates with high methane potential, thus producing more biogas to be valorized in the existent engines. High-strength organics considered suitable co-substrates include waste cooking oil, residual glycerin, or cheese whey from the food industry [49][50][51][52][53][54]. The organic fraction of municipal solid wastes has been extensively studied as co-substrate [55][56][57], but it has the risk of increasing the amount of inert material [58], deteriorating sludge agronomic quality.…”
Section: Cooling Circuit Energy Balancementioning
confidence: 99%
“…AnCoD of multifeedstocks has proved to be a preferred alternative to alleviate the drawbacks of conventional AD by nutrient balance, dilution of toxic materials, and increasing synergistic effects on microorganisms and therefore improving economic benefits through enhanced biomethane production (Bayr et al, 2014; J. Mata‐Alvarez et al, 2014). AnCoD has shown capability to mitigate the problems that may occur in monodigestion such as high ammonia concentration and inhibition of long chain fatty acid by balancing the mixing ratios of the feedstocks and diluting the long chain fatty acids (Chow et al, 2020; Kassongo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%